Affecting Factors on Accountability of Village Fund Allocation Management in Bogor District - rahmatulloh, fajar; Aswar, Khoirul; Ermawati (Information Management and Business Review, 2020)
This research aimed to find out factors which affected accountability of village fund allocation management in Bogor district. Population in this research was village heads and village secretaries in Bogor district. The hypotheses were tested using data surveys from 77 respondents. The analysis technique used multiple linear regression. The findings from this research indicated that the competence of village officials affected the accountability of village fund management. Whereas, society participation and supervisors had no effect on accountability in the management of village fund allocations. This research contributed to the use of village fund allocations in the Indonesian village government. The further research should the interview method to dig deeper into the management of village funds. In addition, further research is expected to expand research to not be only focused on villages in Bogor District.